Quantitative Structure-Activity Relationship, Pharmacokinetics, Drug-likeness, Toxicity, and Molecular Docking Studies of 4-N-(Methyl)-4-Aminoquinoline Derivatives as Antimalarial Compounds - Baari, Muhamad Jalil; Hardiyanti, Devi (UI Scholars Hub, 2025)
Antimalarial drug resistance has encouraged various innovations to develop novel drug compounds that are effective, feasible, and safe, adhering to health standards. One way to do that is by observing and predicting the biological activity of drug compounds using quantitative structure–activity relationship (QSAR) analysis. In this study, QSAR analysis was conducted on the 4-N-(methyl)-4-aminoquinoline derivatives, which effectively inhibit the growth of Plasmodium falciparum as a source of malaria. The research stages involved molecular structure modeling, molecular geometry optimization using the AM1 semi-empirical method, and QSAR descriptor calculations, including electronic (atomic charges (q), HOMO and LUMO energies, polarizability (α), and dipole moment (DM)), hydrophobic (log P), and steric (molecular weight (MW) and molecular refractivity (MR)) parameters. Optimizations and calculations were performed using the Hyperchem software version 8.0. Multiple linear regression (MLR) analysis and external validation generated the best QSAR equation for Model 5: Log (1/IC50) = 11.132 + 42.074qC1 + 853.716qC7 + 444.151qC8 − 1380.73qC9 + 12.577qC16 + 1.155E HOMO − 1.0LogP − 1.365DM. The design of the novel derivatives was based on the QSAR equation’s influential parameters. Subsequently, the pharmacokinetic, drug-likeness, and toxicity aspects were investigated using the SwissADME and ProTox web servers. The results showed that several types of derivative compounds that have been synthesized and designed fulfill these three aspects. Derivatives 1D and 1E with higher antimalarial activities tended to have good pharmacokinetic profiles and drug-like properties but had higher toxicity levels than the other derivatives. Compounds 1B and 1C have relatively lower antimalarial activity but more favorable toxicity profiles. Compound 1A was considered the best potential drug candidate because of its high antimalarial efficacy and relatively low toxicity. The binding affinity of the 4-N-(methyl)-4-aminoquinoline derivatives (−7.5 to −8.3 kcal/mol) with the PfDHODH receptor was close to its native ligand (−10.9 kcal/mol). This is corroborated by the stability and flexibility of PfDHODH-1A obtained from the molecular dynamics (MD) simulations. Therefore, these designed compounds have potential as novel antimalarial drugs.